2022
DOI: 10.47176/mjiri.36.77
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Reality Technology Effects and Features in Cardiology Interventions Training: A Scoping Review

Abstract: Various studies have been conducted in teaching cardiovascular interventions based on virtual reality in recent years, and different results have been obtained. Identifying the features and effects of these interventions in various studies and explaining the existing challenges and gaps can increase the effectiveness of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…According to our ndings, integrating IoT technology, such as wearable devices and mobile applications, into medical education has shown promising outcomes in a variety of elds. Several studies have explored the application of IoT devices such as Google Glass (12,13,16,18), sensors (15,23,38,39), and virtual and augmented reality simulators (19,40,41), highlighting their potential in facilitating surgical / non-surgical medical education through realistic simulations, interactive platforms, and real-time feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our ndings, integrating IoT technology, such as wearable devices and mobile applications, into medical education has shown promising outcomes in a variety of elds. Several studies have explored the application of IoT devices such as Google Glass (12,13,16,18), sensors (15,23,38,39), and virtual and augmented reality simulators (19,40,41), highlighting their potential in facilitating surgical / non-surgical medical education through realistic simulations, interactive platforms, and real-time feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Educational videos provide a unique rst-person perspective, immersing trainees in the learning process and enhancing their ability to visualize surgical procedures effectively. (40,41) Google Glass, as another surgical visualization method, has demonstrated its capability to aid overall learning and offer realistic simulations, particularly for open procedures with limited visibility, allowing instructors to see "blind" regions in the operating eld (11,13). Additionally, its integration into ultrasound-guided processes, like central venous catheter placement, showed that wearers took longer to gain access, required more needle redirections, but exhibited reduced head movements (18).…”
Section: Discussionmentioning
confidence: 99%
“…These implementations are listed in Table 2. [18][19][20][21][22][23][24][25][26][27][28] In addition to training, VR/AR has been utilized in planning minimally invasive surgical procedures. The complex nature of some cases may require 3D models to better illustrate the anatomy of patients and help plan an optimal surgical approach.…”
Section: Current Use Of Metaverse In Medical Educationmentioning
confidence: 99%